2015
DOI: 10.1161/strokeaha.115.008918
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Is the Leading Cause of Death in Rural Gadchiroli, India

Abstract: Background and Purpose-Stroke is an important cause of death and disability worldwide. However, information on stroke deaths in rural India is scarce. To measure the mortality burden of stroke, we conducted a community-based study in a rural area of Gadchiroli, one of the most backward districts of India. Methods-We prospectively collected information on all deaths from April 2011 to March 2013 and assigned causes of death using a well-validated verbal autopsy tool in a rural population of 94 154 individuals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 21 publications
3
73
0
Order By: Relevance
“…[2][3][4][5] India, with one sixth of the world's population, only has approximately 35 stroke units, located mainly in urban centres. 6,7 Consequently most people have no access to specialised stroke care and little access to conventional rehabilitation programs. Given that LMICs only have about 3% equivalent purchasing power to spend on healthcare compared to high-income countries, any new model of stroke rehabilitation should be both sustainable and effective.…”
Section: Family-led Rehabilitation After Stroke In India: a Randomisementioning
confidence: 99%
“…[2][3][4][5] India, with one sixth of the world's population, only has approximately 35 stroke units, located mainly in urban centres. 6,7 Consequently most people have no access to specialised stroke care and little access to conventional rehabilitation programs. Given that LMICs only have about 3% equivalent purchasing power to spend on healthcare compared to high-income countries, any new model of stroke rehabilitation should be both sustainable and effective.…”
Section: Family-led Rehabilitation After Stroke In India: a Randomisementioning
confidence: 99%
“…Linking it to a tertiary or academic centre via tele-stroke will make imaging, evaluation and thrombolysis possible in rural setups [35,84]. …”
Section: Discussionmentioning
confidence: 99%
“…A significant change has occurred in the lifestyle in rural regions of India in the last 2 decades with a high likelihood of increase in the prevalence of stroke. In a recent study, we found that stroke was the leading cause of death and accounted for 14% of all deaths in rural Gadchiroli [11] . In this study, we estimated the prevalence of stroke in rural areas of Gadchiroli, one of the most underdeveloped districts of India.…”
Section: Introductionmentioning
confidence: 99%